2013
DOI: 10.2341/12-432-c
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of Direct Restorations in Stress-Bearing Posterior Cavities: A Retrospective Study

Abstract: The aims of this retrospective clinical study were to compare the longevities of direct posterior amalgam restorations (AMs) and resin composite restorations (RCs) that were subjected to occlusal stresses and to investigate variables predictive of their outcome. A total of 269 AMs and RCs filled in Class I and II cavities of posterior teeth were evaluated with Kaplan-Meier survival estimator and multivariate Cox proportional hazard model. Seventy-one retreated restorations were reviewed from dental records. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 23 publications
3
43
0
2
Order By: Relevance
“…In the present study the longer survival time of CR might result from the fact that the material was used in Class V cavity at a higher proportion (Table 2). Like most previous studies, the median survival time of CR (10.9 years) in Class V restorations was not different from that of GI (10.3 years) in the present study 4,12,13,17. Meanwhile, AM restoration had only 8 Class V restorations that were less influenced from the occlusal force than occlusal restorations.…”
Section: Discussionsupporting
confidence: 65%
“…In the present study the longer survival time of CR might result from the fact that the material was used in Class V cavity at a higher proportion (Table 2). Like most previous studies, the median survival time of CR (10.9 years) in Class V restorations was not different from that of GI (10.3 years) in the present study 4,12,13,17. Meanwhile, AM restoration had only 8 Class V restorations that were less influenced from the occlusal force than occlusal restorations.…”
Section: Discussionsupporting
confidence: 65%
“…Premature failure of these restorations will have significant health and financial implications. Several recent reports indicate that the median longevity of posterior RBCs placed in dental offices worldwide is close to a mere 6 years [2][3][4]. A recent Cochrane review reported that posterior RBCs are almost twice as likely to fail as amalgam restorations [5].…”
Section: Introductionmentioning
confidence: 98%
“…2,3 Although some photopolymerizable resin-based composites (RBCs) have been reported to have excellent longterm results in clinical trials, 1,4,5 the results achieved in dental offices worldwide have been less promising. [6][7][8] If the RBC is undercured, the result will be suboptimal properties for the restorative material that could increase the probability of fracture of the restoration, encourage more secondary caries, increase the wear rate, and result in premature failure. 9 Undercuring is especially of concern for Class II restorations that commonly fail due to bulk fracture or secondary caries at the cervicogingival margin.…”
Section: Introductionmentioning
confidence: 99%